The welfare effects of minority-protective judicial review. (October 2015) - Fox, Justin; Stephenson, Matthew C
Constitutional theorists usually assume that minority-protective judicial review leads to outcomes more favorable to the protected minority and less favorable to the majority. Our analysis highlights an indirect effect of judicial review that complicates this conventional wisdom. Without judicial review, pro-majority and pro-minority leaders adopt different policies. Because judicial review limits the degree to which pro-majority leaders can adopt anti-minority policies, it becomes easier for pro-minority leaders to 'mimic' pro-majority leaders by adopting the most anti-minority policy that the judiciary would uphold. Furthermore, if judicial invalidation of anti-minority policies is probabilistic rather than certain, pro-majority leaders may propose even more extreme anti-minority policies in order to deter pro-minority leaders from mimicking. These effects can sometimes nullify, or even reverse, the assumed relationship between minority-protective judicial review and pro-minority outcomes. When such reversal occurs, majoritarian democrats should favor minority-protective judicial review, while those concerned with protecting unpopular minorities should oppose it.